PO32 Phytochemical study of Siparuna gesnerioides and its antiviral activity against SARS-CoV-2 - Castañeda, Jhon Fredy; G. Leitão, Gilda; G. Leitão, Suzana; Diego Allonso; Fonseca, Thamires; Campos, Mariana; Mendoca, Simony; Silva, Esthella; Sales, Nayara; Fernándes, Diegina (Revista Productos Naturales, 2025)
Species of the genus Siparuna (Siparunaceae) are popularly recognized for their anxiolytic, antioxidant, and antiviral properties1,2. The most active extract was purified by countercurrent chromatography (CCC) using an HTPrep system equipped with a 112 mL column, using a hexane-ethyl acetate-methanol-water solvent system in the ratios 3:7:5:5 and 5:5:5:5 v/v. TFraction XIII was selected for purification, allowing the identification of the flavonoid 3,7-di-O-methyl-kaempferol (kumatakenin). The extract showed a 54% inhibition of the SARS-CoV-2 RBD:ACE2 interaction and a 92% inhibition in the PL pro and 3CLpro assays.
Keywords: Siparunaceae, Siparuna gesnerioides, Countercurrent Chromatography, Nuclear Magnetic Resonance, Antiviral Potential for Covid-19.